Chetna's 30-minute Indian : quick and easy everyday meals - Makan, Chetna (Mitchell Beazley, 2021)
Chetna Makan's bestselling cookbooks combine her creative flavour twists with a love of simple Indian home cooking. Taking inspiration from the eclectic tastes of Indian cuisine, these tempting recipes can all be on the table and ready to eat in less than 30 minutes. Featuring fabulous salads, traditional fast snacks, imaginative toppings for toasts, delicious dals, comforting veggie, fish and meat curries, all-in-one rice dishes, surprising raitas and dips as well as indulgent desserts, there are speedy options for every occasion. With brilliantly useful meal plans included, dishes can be enjoyed on their own or paired together and cooked quickly for an easy feast to enjoy with friends. No complicated methods, just delicious, vibrant and varied food that the whole family can enjoy every single night of the week and in little to no time at all.